Agricultural Communicators in Education - Jim Shaner; Don Esslinger (Journal of Applied Communications, 1979)
Editorial back matter for vol.61, no.4, Dec.-Jan (1979) of The ACE Quarterly, Official Journal of the Agricultural Communicators in Education